The Effect of Strengths-Based Leadership on Employee Performance Through Work Engagement with Leader-Member Exchange as a Moderating Variable at the Sidoarjo Customs and Excise Supervision and Service Office Type B - Riko Priyambada; Purwanto; Sri Rahayu (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the effect of strengths-based leadership on employee performance through work engagement with Leader-Member Exchange as a moderating variable at at the Sidoarjo Customs and Excise Supervision and Service Office Type B. This study employed a quantitative approach with an explanatory research design. The population consisted of all employees, totaling 124 employees, while the sample consisted of 95 respondents determined using the Slovin formula with a 5% margin of error. The sampling technique used was simple random sampling. Data were collected through a questionnaire and analyzed using the SEM-PLS method. The results show that strengths-based leadership has a positive and significant effect on employee performance. Strengths-based leadership also has a positive and significant effect on work engagement. Furthermore, work engagement has a positive and significant effect on employee performance. The results also prove that work engagement mediates the effect of strengths-based leadership on employee performance. In addition, Leader-Member Exchange strengthens the effect of strengths-based leadership on work engagement. These findings indicate that employee performance can be improved by strengthening leadership practices that focus on employee strengths, enhancing work engagement, and improving the quality of relationships between leaders and employees.